PENGARUH CURRENT RATIO, INVENTORY TURNOVER RATIO, DAN LONG-TERM DEBT TO EQUITY RATIO TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SUB SEKTOR KOSMETIK DAN BARANG KEPERLUAN RUMAH TANGGA YANG TERDAFTAR DI BEI: The Effect Of Current Ratio, Inventory Turnover Ratio, And Long-Term Debt to Equity Ratio On Profit Growth In Cosmetics And Household Goods Sub-Sector Companies Listed On The BEI - Sulistianingsih, Sulistianingsih; Huda, Nurul; Mukhlis, Mukhlis (Ganec Swara, 2025)
This study looks at the relationship between the growth of profits in home goods and cosmetics subsector companies listed on the Indonesia Stock Exchange (IDX) and the Current ratio (CR), Inventory turnover ratio (ITO), and Long-Term Debt to Equity Ratio (LTDER) until 2023. This study employs an associative research design and a quantitative methodology. Purposive sampling was used to choose five companies for the study sample. The data came from annual financial report documentation and was subsequently analyzed using multiple linear regression. Based on the results, LTDER had no discernible impact on earnings growth, but CR and ITO had a considerable one. At the same time, earnings growth is significantly impacted by CR, ITO, and LTDER. These results imply that liquidity effectiveness and inventory management have an important role in increasing corporate profits, while the use of long-term debt needs to be managed carefully so as not to suppress profitability. This research is expected to be a consideration for company management, investors, and future researchers in understanding the financial factors that influence earnings growth.